Islamic Boarding School Development: A Review from Management Reshuffle - Susilawati Susilawati; Muh Misbah (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
Change in an organization is very necessary as an effort to improve its quality. In this study, researchers conducted the research on how the efforts of Islamic boarding schools to make changes. This study aims to investigate how the change management of Islamic boarding schools. This research was conducted at Darul Kirom Islamic Boarding School Jatisampurna Bekasi West Java. The research method used is descriptive qualitative research method, which means a research method aimed at describing existing phenomena using triangulation data collection techniques, namely through the main research instrument the researchers themselves are supported by observation, interviews and document studies. Based on the research analysis, conclusions can be drawn, among others: 1) In relation to the management of Islamic boarding school changes have been carried out using an exploration, planning, action and integration approach. This is evidenced by changes in the organizational structure, management of the boarding school, infrastructure, curriculum and human resources at the Darul Kirom Islamic boarding school. 2) Of the two leaderships that have occurred, have a very meaningful role. This is evident in the journey of the Islamic boarding school, each leadership has a role in the changes that continue to develop until now. 3) The driving factors for the change in the Darul Kirom Islamic boarding school are influenced by two factors, namely external factors and internal factors.